A Novel Formononetin Derivative Promotes Anti-ischemic Effects on Acute Ischemic Injury in Mice - Zhao, Lin; Han, Jing; Liu, Jiaqi; Fan, Kechen; Yuan, Tianjie; Han, Ju; Chen, Liangliang; Zhang, Sen; Zhao, Ming; Duan, Jinao (Frontiers in Microbiology, 2021)
Natural flavonoids, formononetin and ononin, possess anti-oxidant, anti-bacterial, anti-inflammatory and neuroprotective effects. Many complications caused by SARS-CoV-2 make patients difficult to recover. Flavonoids, especially formononetin and Ononin, have the potential to treat SARS-CoV-2 and improve myocardial injury. However, their poor water solubility, poor oral absorption, high toxicity, and high-cost purification limit industrial practical application. Succinylation modification provides a solution for the above problems. Formononetin-7-O-β-(6"-O-succinyl)-D-glucoside (FMP), a new compound, was succinyl glycosylated from formononetin by the organic solvent tolerant bacteria Bacillus amyloliquefaciensFJ18 in a 10.0% DMSO (v/v) system. The water solubility of the new compound was improved by over 106 times compared with formononetin, which perfectly promoted the application of formononetin and ononin. The conversion rate of formononetin (0.5 g/L) was almost 94.2% at 24 h, while the yield of formononetin-7-O-β-(6"-O-succinyl)-D-glucoside could achieve 97.2%. In the isoproterenol (ISO) induced acute ischemia mice model, the myocardial injury was significantly improved with a high dose (40 mg/kg) of formononetin-7-O-β-(6"-O-succinyl)-D-glucoside. The lactate dehydrogenase level was decreased, and the catalase and superoxide dismutase levels were increased after formononetin-7-O-β-(6"-O-succinyl)-D-glucoside treatment. Thus, formononetin-7-O-β-(6"-O-succinyl)-D-glucoside has high water solubility, low toxicity, and shows significantly anti-myocardial ischemia effects.